2018
DOI: 10.1177/0363546518778251
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in the Clinical Incidence of Concussions, Missed School Days, and Time Loss in High School Student-Athletes: Part 1

Abstract: Despite sex differences in the clinical incidence of SRCs and time loss from participation in high school sports, the numbers of missed school days are relatively similar between sexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
60
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 25 publications
7
60
0
Order By: Relevance
“…It is worth noting that boys had a significantly higher PARI incidence, injury risk and injury rate than girls (42.0% vs. 25.0%, 0.89 vs. 0.46 and 1.52 vs. 1.28) and different potential risk factors were found between genders, which was consistent with previous research [5,17]. Compared with girls, boys tend to be more motivated and active to engage in PA [26,27], which might elevate their exposure to PARI.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It is worth noting that boys had a significantly higher PARI incidence, injury risk and injury rate than girls (42.0% vs. 25.0%, 0.89 vs. 0.46 and 1.52 vs. 1.28) and different potential risk factors were found between genders, which was consistent with previous research [5,17]. Compared with girls, boys tend to be more motivated and active to engage in PA [26,27], which might elevate their exposure to PARI.…”
Section: Discussionsupporting
confidence: 91%
“…However, the adverse effects of PA participation have also been documented in numerous studies—the increased risk of physical activity-related injuries (PARI) [3,4]. Previous studies revealed that PARI could place a great burden on children and adolescents, resulting in absence from classes and normal PA engagement, physical discomfort, medical consultation and hospitalization [5,6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this retrospective study are mostly consistent with previous studies in relation to gender differences in the incidence of concussions [6,10,17,18]. Overall, for this study more females sought treatment for a concussion compared to males.…”
Section: Discussionsupporting
confidence: 90%
“…However, there is substantial research to suggest there are sex differences in clinical outcomes following a concussion. Female athletes may have an increased risk of injury 6,7 and prolonged recovery time 8,9 and report different symptom profiles compared with male athletes 10 ; however, these findings are not conclusive, and differences may be more prevalent in younger populations. [11][12][13] Although there is evidence of sex differences in clinical presentation, it is currently unclear whether they are associated with underlying differences in concussion neurobiology between men and women.…”
Section: Introductionmentioning
confidence: 99%